2021
DOI: 10.1017/s0007114521002154
|View full text |Cite
|
Sign up to set email alerts
|

Fruit and vegetable consumption before and during pregnancy and developmental delays in offspring aged 2 years in Japan

Abstract: The association between fruit and vegetable consumption before and during pregnancy and offspring’s physical growth has been well reported, but no study has focused on offspring’s neurological development. We aimed to explore the association between maternal fruit and vegetable consumption before and during pregnancy and developmental delays in their offspring aged 2 years. Between July 2013 and March 2017, 23,406 women were recruited for the Tohoku Medical Megabank Project Birth and Three-Generation Cohort St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…First, differences in nutrient intake due to breakfast frequency may have contributed to this association. Vegetables and fruits are rich in a variety of vitamins, minerals and carotenoids [34], and one study showed that vegetable and fruit intake was associated with a lower risk of developmental delay in children [9]. Fish and PUFAs such as DHA and EPA have been reported to be bene cial for neurodevelopment in children [10,35], and one study showed that folic acid and multivitamin intake before and during pregnancy is bene cial for child development [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, differences in nutrient intake due to breakfast frequency may have contributed to this association. Vegetables and fruits are rich in a variety of vitamins, minerals and carotenoids [34], and one study showed that vegetable and fruit intake was associated with a lower risk of developmental delay in children [9]. Fish and PUFAs such as DHA and EPA have been reported to be bene cial for neurodevelopment in children [10,35], and one study showed that folic acid and multivitamin intake before and during pregnancy is bene cial for child development [8].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated associations between nutrients or foods consumed by pregnant women and developmental delays in the child, including folic acid and multivitamin supplements [8], vegetables, fruit [9],…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, inadequate fruit and vegetable intake is associated with a greater risk for micronutrient deficiencies, lower GWG [46], lower neonatal birth weight [47][48][49] and length [49], a greater risk of giving birth to low birth weight (LBW) infants [47], an unfavorable infant gut microbiome [50], as well as greater odds of their offspring's developmental delays [51]. Previous Greek data revealed an inadequate fruit and vegetable intake among pregnant women [16], indicating the need for nutrition education.…”
Section: Nutritional Risk Factors During Pregnancymentioning
confidence: 99%
“…Epidemiological studies confirmed that MD was beneficial to multiple offspring health problems (e.g., preterm delivery, fetal birth weight, early growth, and cardiometabolic risk) ( 8 , 9 ). Beneficial foods in the Mediterranean diet, such as fruits and vegetable consumption during pregnancy, have been shown to support neurodevelopment in offspring ( 10 ). A randomized controlled trial (RCT) study investigated that nuts and olive oil consumption were associated with better nervous system function in humans ( 11 ).…”
Section: Introductionmentioning
confidence: 99%